농업인 포장디자인 교육 의식 분석을 통한 역량강화 교육프로그램 표준안 개발 - 진혜련; Hyr Ryeon Jin; 채혜성; Hye Sung Chae (기초조형학연구, 2016)
농촌의 6차 산업 활성화와 직거래 증가로 인하여 농산물의 품질향상을 위해 농업인 역량범위가 확대되고 있다. 이에 최근 정부기관 중심으로 농업인 역량강화를 위해 포장 및 브랜드 등 디자인 관련 교육이 한시적으로 운영되고 있으며 이 전 연구를 통해 농업인 디자인 교육 기관 20개소 현황조사 결과 디자인교육프로그램 개발에 관한 요구도가 높게 나타났다. 이에 본 연구는 농업인 의식을 분석하고 디자인, 교육 전문가 협의를 통해 농업인 포장디자인 역량강화 교육프로그램을 개발하였다. 농업인 250명(유효표본 223명)을 대상으로 교육여부, 만족도, 활용 및 참여의지, 요구도 등을 설문으로 구성하여 조사를 실시하였고 전문가협의는 3회에 걸쳐 디자인전문가협의, 교육전문가협의, 농업인디자인교육전문가협의로 실시하였다. 그 결과 교육여부는 41.3%가 받은 경험이 있으며 교육 횟수, 내용, 시기, 방식 등의 만족도가 7점 기준으로 4점 이하로 낮게 나타난 반면 디자인 교육 활용 및 의지는 6점 이상으로 높게 나타났다. 교육요구도 분석 결과 회차는 2회 이상 ~ 4회 미만이 50.7%로 높게 나타났고 시기는 1월~3월시기로 현황과 다르게 나타났으며 교육방식은 현장견학이 30.5%로 가장 높았고 이론, 실습 등 비슷한 비율로 나타났다. 본 결과를 바탕으로 3회차 협의회를 통해 수준(기초-심화-응용), 단계(이론-실습-현장견학-토론)를 설정하고 각 수준과 단계에 해당하는 역량을 정의하고 교과목을 구성하여 농업인 포장디자인 교육프로그램 표준안을 개발하였다. Due to the invigoration of the Sixth Industry in farming villages and the increased amount of direct marketing, the scope of farmers` capability is expanding in quality improvement of agricultural products. Government agencies are accordingly and continuously operating education related to designs for packing and branding in order to strengthen the capability of farmers. Previous studies, based on the status reports from twenty design education institutions for farmers, have shown high demands for the development of design educational programs. Thus, this study has analyzed farmers` awareness of packing, and has consulted with the experts on design and education to help strengthen their capability of packing design by further developing the educational program. Two-hundred fifty farmers (valid samples: 223) were surveyed with questionnaires on training, satisfaction, utilization, and willingness to participate. The study held three rounds of conferences, which included Design Expert Consultation, Education Specialist Conference, and Conference of Professionals for Farmers` Design. Each conference found the following: 41.3% of the subjects had experienced certain design training, including satisfaction with the time and content. The timing and the method of training was lower than 4 out of 7 points. In contrast, their interest in the application of design education was higher than 6 points. Education demand showed that an estimated 50.7% desired around two to three more occasions of training, a considerably high percentage. The subjects requested that the training be from January to March, which differentiates from the current training schedule. 30.5% wanted the training method of the on-the-spot study, which was the highest. Theory education and practice showed a similar rate. Based on these findings, the third consultation was held to establish Levels (Basic, In-depth, and Application) and Phases (Theory, Practice, On-the-spot Study, Discussion). The consultation helped strengthen the farmers` capability in understanding the curriculum, levels, and phases, and allowed them to reach the standard in the educational program and to develop packing design skills.